1982
DOI: 10.1017/s002221510009349x
|View full text |Cite
|
Sign up to set email alerts
|

Extra-nasopharyngeal extensions of angiofibroma

Abstract: Four cases of NPA with extra-nasopharyngeal extensions have been presented, two of which had an intracranial extension. On of the cases with intracranial extension underwent a transtemporal craniotomy removal and four temporal fossa. The other three cases were managed by the sublabial and transantral routes. Methods of pre-operative diagnosis of such extensions have been discussed and the importance of pre-operative recognition of extension in every NPA has been emphasized. Various approaches to the lateral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In 5 of our patients with orbital invasion, the route of spread to the orbit was through the inferior orbital fissure as the result of the upward growth of the tumor. This pathway of extension had already been observed, 10 and our prevalence rate of orbital invasion compares well with other studies from the otolaryngological literature. Lloyd et al 5 stated that the orbit is invaded in 27% of cases and Herman et al, 3 analyzing CT scans of 44 patients, found a rate of 31.2% of orbital involvement in JNA extension.…”
Section: Orbital Invasion By Juvenile Nasoangiofibromasupporting
confidence: 91%
“…In 5 of our patients with orbital invasion, the route of spread to the orbit was through the inferior orbital fissure as the result of the upward growth of the tumor. This pathway of extension had already been observed, 10 and our prevalence rate of orbital invasion compares well with other studies from the otolaryngological literature. Lloyd et al 5 stated that the orbit is invaded in 27% of cases and Herman et al, 3 analyzing CT scans of 44 patients, found a rate of 31.2% of orbital involvement in JNA extension.…”
Section: Orbital Invasion By Juvenile Nasoangiofibromasupporting
confidence: 91%
“… 7,8 Four routes to the cranium have been described in the literature from the tumor's point of origin at the posterolateral wall of the roof of the nasal cavity. 5,9,10 Tumor extension may occur 1 from the infratemporal fossa through the floor of the middle cranial fossa, 9 from the pterygomaxillary fissure and infratemporal fossa into the superior and inferior orbital fissures, 9 through direct erosion of the sphenoid sinus into the region of the sella turcica and cavernous sinus, 9,10 or more rarely, 4 along the horizontal lamina of the ethmoids and cribriform plate into the anterior cranial fossa. 10 Depending on which pattern of spread the tumor pursues, the growth will come to lie either lateral 1,2 or medial 3,4 to the cavernous sinus and internal carotid artery.…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 Tumor extension may occur 1 from the infratemporal fossa through the floor of the middle cranial fossa, 9 from the pterygomaxillary fissure and infratemporal fossa into the superior and inferior orbital fissures, 9 through direct erosion of the sphenoid sinus into the region of the sella turcica and cavernous sinus, 9,10 or more rarely, 4 along the horizontal lamina of the ethmoids and cribriform plate into the anterior cranial fossa. 10 Depending on which pattern of spread the tumor pursues, the growth will come to lie either lateral 1,2 or medial 3,4 to the cavernous sinus and internal carotid artery. 5,8,9 Although surgery is considered by most to be the treatment of choice for JNA, the potential morbidity and mortality associated with surgical resection of intracranial tumors have prompted others to investigate the role of radiation therapy for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Less commonly, the angiofibroma may extend through the roof of the sphenoid sinus and occupy a position medial to the internal carotid artery and lateral to the pituitary gland (10). Whereas CT scanning is the initial imaging modality, MRI and angiography have become increasingly useful in delineating and defining the extent of the tumor.…”
Section: Discussionmentioning
confidence: 99%